Urbanization in South and South West Asia Characteristics and Consequences - Singh, Ram Bali (National Geographical Journal of India, 2022)
Forces of urbanization, industrialization and socio-economic transformation seem to be mutually reinforcing. However this has not happened in many developing countries more so in some countries of South and South West Asia. These countries witnessed the evolution and growth of one of the earliest urban-based civilizations during the ancient period and development of processing and manufacturing activities during the pre-colonial period. During the colonial period the spatial system that could develop and the economic structure that could evolve did not conform to the national needs. The rural-agriculture sector was neglected and the urban-industrial sector remained constricted resulting in a dualistic nature of the national space economy. A lopsided pattern of spatial linkages and an unarticulated spatial system strengthened further the forces of dualism. The countries of the South and South West Asia are now implementing development strategies to remedy the situation and achieve the much sought after goal of sustainable urbanization and a balanced spatial distribution of population and development opportunities. The present paper examines the level of urbanization, rate of urban growth and size distribution of urban centers in 10 countries of the South and South West Asia during 1975-2025 and highlights the consequences flowing from the existing pattern with an objective to guide the formulation of future development policies